Pengaruh Pendekatan Contextual Teaching and Learning terhadap Pemahaman Konsep Matematika Peserta Didik Kelas VIII SMPN 10 Padang - INTAN MUTHIA WARDI (Jurnal Edukasi dan Penelitian Matematika, 2020)
Understanding the concept is a basic ability that must be possesed by every student. In fact, in reality understanding mathematic concept of students in grade VIII at SMPN 10 Padang still low. Based on observation learning is still centered on the teacher, the teacher actively provides information to students, while students are still passive in learning. One of the efforts made to improve students understanding of concept is to apply the Contextual Teaching and Learning (CTL) approach. The purpose of this study is to describe whether understanding mathematic concepts of students who learn by CTL approach is better than who learn by conventional learning. The type of the research was a quasi-experimental design with Static Group Design. Based on the result of the data analysis, it was concluded that understanding mathematic concepts of students who learn using the CTL approach is better than students who learn by conventional learning.  Keywords—, Understanding of mathematical concepts, the Contextual Teaching and Learning approach, the conventional learning.